Measurement of Stress Relief during Scented Cosmetic Product Application Using a Mood Questionnaire, Stress Hormone Levels and Brain Activation - Springer, Arielle; Hoeckmeier, Laura; Schicker, Doris; Hettwer, Stefan; Freiherr, Jessica (Cosmetics, 2022)
Nowadays, consumers’ well-being plays a decisive role in the purchase of cosmetic products. Although factors influencing consumers’ well-being are very subjective, companies strive to develop their products in such a way that a positive effect is likely. Therefore, methods are required to objectively explore and scientifically prove the product’s performance on humans. In this placebo-controlled study, a method was developed to evaluate relaxation or stress relief associated with one olfactory ingredient of a cosmetic product (face cream). Our experimental protocol included product testing in 25 healthy females, while an emotion questionnaire, analysis of saliva samples regarding the concentration of the hormones cortisol and α-amylase and mobile EEG measurement for quantification of the alpha brain waves before and after stress induction were conducted. It was shown that with this experimental design, the sample with the ingredient produced significant stress relief, as evidenced by significantly less negative emotion, significantly lowered cortisol levels and showed a trend towards a significant increase in alpha activity compared to placebo application. Our data provide evidence that this method is suitable for analyzing the differences between the two samples. In the future, this method can be utilized in the current or a further optimized form to evaluate the psychophysiological effects of cosmetic products on humans.
CRIS-Team Scopus Importer:2022-11-04
Keywords: alpha waves; amylase; aroma; brain activity; cortisol; EEG; fragrance; neuroscience; positive mood; relaxation; scent; skin care; well-being